Sikap Masyarakat Terhadap Program Kegiatan Komunitas Blus (Belajar Luar Sekolah) - Siti Khotimah; Adelina Hasyim; Yunisca Nurmalisa (Jurnal Kultur Demokrasi, 2018)
The purpose of this study was to analyze how people's attitudes towards the Community Blus (Learning Outside School) program as a means of empowering children's literacy skills in Taman Endah Village, Purbolinggo District, East Lampung Regency. This research uses descriptive method with a quantitative approach. A total of 31 respondents. Data collection techniques using questionnaire techniques and interview techniques. Technical data using interval and percentage formulas. The results showed that people's attitudes towards the Community Blus (Learning Outside School) program as a means of empowering children's literacy skills were supportive, as (1) Community understanding of the Blus Community (Learning Outside School) program tends to understand. (2) The feeling of the community towards the Community Blus (Learning Outside School) program as a means of empowering children's literacy abilities tends to be happy. (3) The tendency to act the community towards the Community Blus (Learning Outside School) program as a means of empowering children's literacy skills tends to support.Tujuan penelitian ini adalah menganalisis bagaimana sikap masyarakat terhadap program kegiatan Komunitas Blus (Belajar Luar Sekolah) sebagai wadah pemberdayaan kemampuan literasi anak di Desa Taman Endah Kecamatan Purbolinggo Kabupaten Lampung Timur. Penelitian ini menggunakan metode deskriptif dengan pendekatan kuantitatif. Sampel berjumlah 31 responden. Teknik pengumpulan data menggunakan teknik angket dan teknik wawancara. Teknis data menggunakan rumus interval dan persentase. Hasil penelitian menunjukkan bahwa sikap masyarakat terhadap program kegiatan Komunitas Blus (Belajar Luar Sekolah) sebagai wadah pemberdayaan kemampuan literasi anak bersikap mendukung, sebagaimana (1) Pemahaman masyarakat terhadap program kegiatan Komunitas Blus (Belajar Luar Sekolah) cendrung paham. (2) Perasaan masyarakat terhadap program kegiatan Komunitas Blus (Belajar Luar Sekolah) sebagai wadah pemberdayaan kemampuan literasi anak cendrung senang. (3) Kecendrungan bertindak masyarakat terhadap program kegiatan Komunitas Blus (Belajar Luar Sekolah) sebagai wadah pemberdayaan kemampuan literasi anak cendrung mendukung.Kata Kunci: komunitas, literasi, masyarakat.